BELIEFS ABOUT PSYCHOLOGICAL MATURITY AND ADULT DEVELOPMENT - Zacarés González, Juan José; Serra Desfilis, Emilia (Anales de Psicología / Annals of Psychology)
Normative beliefs about the human life course, especially the psychological change expected, are important for the self-perception of adult subject of his own development. This empirical study concerns the lay perspective, and has the aim of inquiring into implicit knowledge about psychological maturity that is adopted by the Spanish adult subjects. Likewise,there are attempts to relate these cognitive contents to two sociodemographic variables (age and sex). Lay knowledge was speficied as implicit theories, in the form of beliefs about the process of psychological maturation, that are.assumed by adults. A ad hoc questionnaire was devised, with the aim of evaluating: the CCM (Beliefs about Psychological Maturity Questionnaire). Four groups of beliefs or implicit theories were identified through ACP: passive-external, humanistic, relativisticsituational and active-internal. In general, the results show significant and important age differences in beliefs, whereas sex differences were less significant.